2012
DOI: 10.1002/eqe.2200
|View full text |Cite
|
Sign up to set email alerts
|

Damping‐adjusted combination rule for the response spectrum analysis of base‐isolated buildings

Abstract: SUMMARY The classical response spectrum method continues to be the most popular approach for designing base‐isolated buildings, therefore avoiding computationally expensive nonlinear time‐history analyses. In this framework, a new method for the seismic analysis and design of building structures with base isolation system (BIS) is formulated and numerically validated, which enables one to overcome the main shortcomings of existing techniques based on the response spectrum method. The main advantages are the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…In this section, for demonstration purposes, a base-isolated building taken from Ref. [42] is analyzed as case study.…”
Section: A Case Study: Reliability Analysis Of a Base Isolated Mdof S...mentioning
confidence: 99%
See 2 more Smart Citations
“…In this section, for demonstration purposes, a base-isolated building taken from Ref. [42] is analyzed as case study.…”
Section: A Case Study: Reliability Analysis Of a Base Isolated Mdof S...mentioning
confidence: 99%
“…Detailed information on the spatial distribution of mass and stiffness can be found in Ref. [42] and, as much as possible, a notation consistent with Ref. [42] has been adopted in what follows.…”
Section: A Case Study: Reliability Analysis Of a Base Isolated Mdof S...mentioning
confidence: 99%
See 1 more Smart Citation
“…The complex mode superposition can give several advantages for the evaluation of seismic response, and it was found to be competitive in terms of computational effort with direct integration methods [41]. As an alternative, Muscolino et al [42] proposed an improved response spectrum method (RSM) for the seismic analysis and design of building structures with base isolation system. This method consists of a two-stage transformation of coordinates in parallel with a Damping-Adjusted Combination (DAC) rule.…”
Section: Mathematical Problems In Engineering 15mentioning
confidence: 99%
“…Thus, it may lead to unacceptable inaccuracies when the modal frequencies of the structure are close to each other (e.g., in the first three rigid-body modes for base-isolated buildings). In order to overcome these problems, Muscolino et al [21] proposed an improved Response Spectrum Method based on a two-stage transformation of coordinates in parallel with a Damping-Adjusted Combination (DAC) rule. As far as the response history analysis is concerned, it must be observed that the baseisolated structures are typically nonlinear and nonclassically damped systems.…”
Section: Dynamic Analysis Proceduresmentioning
confidence: 99%